Cause of Post-Traumatic Stress Disorder Portrayed in the Movie Cherry by Russo Brothers - Dita Marwati; Gaguk Rudianto (Institut Agama Islam Negeri Palopo, 2022)
The theory used in this research was proposed by Freud, (1921) to analyze Post-Traumatic Stress Disorder found in the movie â€œCherryâ€ movie by Russo Brothers. The movie will be the data source to analyze cause of Post-Traumatic Stress Disorder. Mental illness is the main topic that sometime portrayed in the movie or novel. This research will be focused on the cause of Post-Traumatic Stress Disorder from the utterances and narrations by the characters in the movie. The research will be used descriptive qualitative method of the research by (Creswell, 2013) to conduct the data. The researchers will be analyzed the utterances and narrations from the characters in the movie â€œCherry.â€ The utterances and narrations discovered in the movie will be classified used theory causes of Post-Traumatic Stress Disorder proposed by Davison, (2012) which were genetic, environmental, brain structure and psychological causes. Â The observational method and non-participatory technique as the methods of collecting data will be used in this research. The result will be discovered that there were 10 utterances, narrations, or actions of cause of Post-Traumatic Stress Disorder by the characters in the movie. They are included 3 data discovered as genetic causes and 7 data discovered as environmental causes.